2010
DOI: 10.1155/2010/405469
|View full text |Cite
|
Sign up to set email alerts
|

Update on Instrumentations for Cholecystectomies Performed via Transvaginal Route: State of the Art and Future Prospectives

Abstract: Natural Orifice Transluminal Endoscopic Surgery (NOTES) is an innovative approach in which a flexible endoscope enters the abdominal cavity via the transesophageal, transgastric, transcolonic, transvaginal or transvescical route, combining the technique of minimally invasive surgery with flexible endoscopy. Several groups have described different modifications by using flexible endoscopes with different levels of laparoscopic assistance. Transvaginal cholecystectomy (TVC) consists in accessing the abdominal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the general surgery literature, Ghezzi et al reported no increase in infection rate for transvaginal removal of the appendix, and Pulvirenti et al similarly noted no increase in infection rate when removing the gallbladder transvaginally. 6 , 7 These findings were affirmed in the gynecologic literature: a 2012 review of transvaginal specimen retrieval for gynecologic procedures demonstrated no significant increase in infection rates or sexual dysfunction. 2 , 17 Furthermore, these findings are consistent with prior studies that have found no increased incidence in sexual dysfunction and dyspareunia after total hysterectomy, where a colpotomy incision is created, versus a supracervical hysterectomy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the general surgery literature, Ghezzi et al reported no increase in infection rate for transvaginal removal of the appendix, and Pulvirenti et al similarly noted no increase in infection rate when removing the gallbladder transvaginally. 6 , 7 These findings were affirmed in the gynecologic literature: a 2012 review of transvaginal specimen retrieval for gynecologic procedures demonstrated no significant increase in infection rates or sexual dysfunction. 2 , 17 Furthermore, these findings are consistent with prior studies that have found no increased incidence in sexual dysfunction and dyspareunia after total hysterectomy, where a colpotomy incision is created, versus a supracervical hysterectomy.…”
Section: Discussionmentioning
confidence: 89%
“… 5 Prior case reports and case series have documented successful transvaginal retrieval of various organs, including the appendix, gallbladder, kidney, stomach, pancreas, and colon. 6 11 Studies comparing traditional laparoscopic approaches with transumbilical specimen retrieval versus transvaginal approaches have demonstrated decreased postoperative pain from using the transvaginal approach. 12 14 Furthermore, studies have demonstrated no increased risk of postoperative infection or incidence of sexual dysfunction or pelvic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Operative instruments and endoscopes working in parallel create the possibility for interferences, hinders effective manipulation, and does not facilitate triangulation as movement is constrained to the long axis. 58,[94][95][96] This may significantly limit exposure, dissection, and field of view potentially increasing the risk of injury while instruments are out of sight. 97 In a task-analysis of CLC versus TVC, Nemani et al demonstrated increased errors in the TVC group due to instruments being out of sight whereas the CLC group had more errors due to lack of progress.…”
Section: Discussionmentioning
confidence: 99%
“…7,18,102 Some authors have described manual straightening of endoscopic clips to mitigate this issue and facilitate placement, however, while successful, this technique is inefficient and not ideal given that it requires modifying a manufactured product. 18,95 Prototype flexible clip appliers capable of complete occlusion have been described 103 including one with a zero-gap clip. 97 Of note, clip placement using this prototype took 9 minutes, significantly longer than laparoscopic clip placement.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid NOTES, with an additional port through the umbilicus, appeared to increase instrumentation and safety, as the entry through the vagina or stomach can be visually controlled. Several reports found hybrid NOTES to be applicable in general surgery, as for cholecystectomy and appendectomy and several technical reports on instrumentation for NOTES can be found ( Figures 3 and 4) [29,30]. The ENDOSAMURAI by Olympus is a platform with two arms fitted to the tip of an endoscope that includes forceps channels in addition to the endoscope itself and its two arms.…”
Section: Natural Orifice Transluminal Endoscopic Surgery (Notes)mentioning
confidence: 99%